(untitled) (UUM Journal of Legal Studies, 2020)
The role of labour and industrial laws is of paramount importance when the economy of a country depends largely on its industrial sector. In addition, the necessary infrastructure for investments in natural resources is also important. It is clear that if these essential elements are not available then the growth of the industrial sector is hardly feasible. Besides all these, the proper management of labour is essential for the growth of the industrial sector including managing labour issues. Thus timely disposal of labour disputes is also important. However, in most cases labour law disputes are not solved within a short period of time causing remedies which are essential for these disputes to be delayed. Labour laws are important from the Bangladesh perspective as it is crucial for the industrial development of the country. Labour is an important part of an industry and as such an industry without labour would be inconceivable. Although labour rights are crucial in Bangladesh, employees are ignorant about their rights as they do not have adequate education and knowledge about labour laws. This is a huge problem. This paper aims to narrow the gap between existing laws and the real scenario relating to industrial practices in Bangladesh.